IDENTIFIKASI BAHAYA MENGGUNAKAN METODE HAZARD IDENTIFICATION RISK ASSESSMENT AND DETERMINING CONTROL (HIRADC) PADA LABORATORIUM REKTIFIKASI ORTOTIK PROSTETIK POLTEKKES KEMENKES SURAKARTA - Munawaroh, Siti; Triyanta, Triyanta; Sari, Dewi Puspito (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The Orthotic Prosthetic Rectification Laboratory at the Ministry of Health Polytechnic of Surakarta functions to modify the positive casts needed in the manufacture of prostheses and orthoses. The processes carried out in this laboratory include negative cast casting (filling) and rectification. Based on data from the laboratory, between November 2022 and May 2024, 76 work accidents were recorded by students during practicums. This study aims to identify hazards using the HIRADC (Hazard Identification, Risk Assessment, and Determining Control) method at the Orthotic Prosthetic Laboratory of the Ministry of Health Polytechnic of Surakarta. This study uses a qualitative descriptive case study approach conducted in July 2024, involving 5 informants: 1 Educational Laboratory Assistant, 1 Head of Laboratory, 1 Practical Lecturer, and 2 practical students. The focus of the study is to identify hazards through the HIRADC method, which includes hazard identification, risk assessment by determining the likelihood and severity, and risk control based on the hierarchy of control. Qualitative data analysis includes data reduction, data review, and drawing conclusions. The results of the study revealed various potential hazards: 20 physical hazards, 18 chemical hazards, 1 biological hazard, 8 ergonomic hazards, and 1 psychological hazard. The risk assessment showed 20 low risks, 19 moderate risks, and 2 high risks. Hazards with high risks are related to negative cast casting, while moderate and low risks are found in other activities in the laboratory. Recommended controls include the use of personal protective equipment (PPE), safe engineering design, and administrative controls. Suggestions for future improvements include developing work procedures, ensuring the availability and good condition of PPE, installing K3 posters, supervising activities, and training and ceztification of K3 Experts.Keywords: Hazard, Determining Control, Risk Assessment.